Disease-driven restructuring of the gut microbiome underlies inflammatory bowel disease dysbiosis - Ding, Zixu; Ren, Ke; Xu, Yixue; Feng, Tong; Cui, Kuiqing; Liu, Qingyou; Liao, Cun (Frontiers in Microbiology, 2026)
BackgroundInflammatory bowel disease (IBD) is a chronic and recurrent intestinal disorder with rising global incidence, yet its complex pathogenesis remains poorly understood, underscoring the need to clarify the microbial mechanisms underlying intestinal inflammation. IBD is associated with a profound imbalance of the gut microbial ecosystem. However, the ecological and functional remodeling of the gut microbiota during IBD progression remains unclear. This study used metagenomic sequencing to investigate microbial composition, functional capacity, and ecological interactions in the gut microbiota of IBD patients compared with healthy individuals.ResultsThe IBD group exhibited significantly reduced microbial diversity and a distinct community structure compared with healthy controls. Pro-inflammatory genera such as g_Fusobacterium (p < 0.001) and g_Morganella (p < 0.001) were enriched, whereas short-chain fatty acid producing bacteria, including g_Ruminococcus (p < 0.0001) and g_Agathobacter (p < 0.0001), were markedly depleted. Functional annotation revealed decreased abundance of carbohydrate-active enzymes (GH3, GH44, GH53, and GH77; all p < 0.05) associated with polysaccharide degradation, together with enrichment of pathways related to immune activation and inflammation, such as the JAK–STAT and chemokine signaling pathways (p < 0.05). Co-occurrence network analysis further showed that IBD-associated microbes formed positively correlated clusters dominated by inflammatory taxa, whereas healthy microbiota were organized around SCFA-producing commensals.ConclusionCompared with healthy individuals, the gut microbiota of IBD patients undergoes functional reprogramming characterized by loss of metabolic versatility and enrichment of inflammation-related pathways. These findings provide new insights into the ecological and metabolic mechanisms through which the gut microbiota contribute to intestinal inflammation and disease progression.